Does a change in ventricular size predict a diagnosis of cerebral venous thrombosis-related acute intracranial hypertension? Results of a retrospective imaging study. (October 2019) - Zheng, Ying-mei; Chen, Jing; Yuan, Ming-gang; Wu, Zeng-jie; Dong, Cheng
Background: Acute intracranial hypertension (IH) is commonly found in patients with cerebral venous thrombosis (CVT). Some magnetic resonance imaging (MRI) findings that are suggestive of acute IH and are thus important for planning treatment and improving clinical outcomes have been reported; however, the significance of changes in ventricular size in the presence of acute CVT-related IH remains unclear. Purpose: To investigate changes in ventricular size in patients with CVT-related IH by MRI and to determine whether such changes are predictors of IH in these patients. Material and Methods: Forty patients with CVT-related IH and 40 age- and sex-matched healthy volunteers who had undergone T1-weighted volumetric MRI were enrolled in this retrospective study and allocated to one of the following three groups: IH pre-treatment group (Day 1); IH post-treatment group (Day 30); and controls. Data concerning the volume of the ventricular system were compared between the groups. Results: The volumes of the ventricular system in the three groups were 16.10 ± 8.22 cm 3, 16.14 ± 8.14 cm 3, and 15.10 ± 4.75 cm 3, respectively. The volumes of the ventricular system were similar in pre-treatment and post-treatment patients with IH ( P  = 0.982) and controls ( P  = 0.446). Conclusion: The lack of a significant difference in ventricular system volumes between the three study groups suggests that changes in ventricular size are neither a reliable MRI predictor of acute CVT-related IH caused by CVT or a predictor of the short-term prognosis (30 days) of this condition.